Suicide Squad. Hell to pay [videorecording (Blu-Ray + DVD)] - Burnett, Alan; Slater, Christian; Williams, Vanessa; Brown, Billy (Actor); Van Straten, Kristin Bauer, 1966- (Warner Bros. Home Entertainment, 2018)
The Suicide Squad is sent on a mission to retrieve a mystical object so powerful, they're willing to risk their own lives to steal it for themselves.